Pendekatan Mind Mapping : Proses Pembelajaran Bimbingan Belajar Kumon - Fauzi, Taty; Nurbaiti Nurbaiti; Rahmah Novianti; Natasha Intania (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
So far the education system in Indonesia has not optimally implemented: classroom learning so it does not accommodate the needs of each student. It is proven that remedial learning is still in demand to increase skills outside of class hours. This condition is a serious enough problem that parents are looking for options to increase their children's abilities through tutoring. Schools in all educational units should be able to apply the concept of differential learning, namely learning that prioritizes the learning needs of age to face challenges. However, this does not mean that differentiation learning provides different treatment. In fact, every child is unique, has different styles, interests and abilities. The results of  the counseling at Kumon prove the speed of students in answering 100 questions in 5 minutes. On average, students complete their assignments. Then the child learns to the next level. If they cannot reach the time limit, students will be motivated to repeat it until they meet the minimum time limit. The mind mapping and Kumon methods have similarities